(untitled) - Spring, Joel H. (Boston, 2004)
Based largely on material from Joel Spring's The American School 1649-2000, Fifth Edition, Deculturalization and the Struggle for Equality is a concise history of Anglo American racism and school policies affecting dominated groups in the United States. Spring focuses on the educational, legal and social construction of race and racism, and on educational practices related to deculturalization, segregation, and the civil rights movement. He emphasizes issues of power and control in schools and how the dominant Anglo class has stripped away the culture of minority peoples in the US and replaced it with the dominant culture.
Keywords: Tuổi vị thành niên,Minorities,Discrimination in education,Segregation in education,Multicultural education; Giáo dục,Lịch sử,Education,History,History,History,History; Nước Mỹ,United States,United States,United States,United States